Influence of environmental parameters on benthic macroinvertebrate assemblages in the headwaters of Bagmati river, Kathmandu valley, Nepal - Rai, A.; Shah, D. N.; Shah, R. D. T.; Milner, C. (Banko Janakari, 2019)
The distribution of benthic macro invertebrates (BMIs) is affected by various environmental factors. Understanding their response to these factors is a key to assessing freshwater quality. The aim of this research is to understand the influence of different environmental parameters on BMIs assemblages in the headwaters of Bagmati River. The BMIs were sampled following a multi-habitat sampling protocol and the – hydrological and physico-chemical parameters were measured using standard methods. The relationship between environmental parameters and macro invertebrate assemblages was analyzed through Multivariate analysis - Redundancy Analysis and Variation Partitioning. Stream discharge, pH and Dissolved Oxygen were selected for multivariate analysis through backward elimination method. pH and Dissolved Oxygen were important contributing factors explaining the variation in BMIs community. Physico-chemical parameters were found to be the most important group of variables explaining the variation in macro invertebrate assemblages. Only about twenty-five per cent of the variation in the BMIs community was explained by the model so the parameters studied here do not have a high degree of explanatory power.